Multiscale Finite Element Method for Subdivided Periodic Elastic Structures of Composite Materials (Journal of Computational Mathematics, 2001)
In this paper, from the view of point of macro- and meso-scale coupling, we discuss the mechanical behaviour for subdivided periodic elastic structures of composite materials. A multiscale numerical method and its error estimate are reported. Finally, numerical experiments results  strongly support the theoretical ones presented in the paper.